ANALISIS FAKTOR RISIKO KEJADIAN PENYAKIT DIABETES MELLITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS WAWOTOBI KABUPATEN KONAWE TAHUN 2020 - Andi Ulfryza Dwi Riwansyah; La Ode Muhamad Sety; Jusniar Rusli Afa (FKM Universitas Halu Oleo, 2021)
Type 2 diabetes mellitus is a chronic disease that occurs when the pancreas does not produce enough insulin or if the body cannot effectively use the insulin it produces. This research aims to analyze the risk factors against type 2 diabetes mellitus disease in the working area of Puskesmas Wawotobi Konawe District in 2020. This study used a case control study design. The population in this study were all patients who checked themselves at the Public Poly of Puskesmas Wawotobi Konawe Regency in January to August 2020. The sample in this research totalled 120 samples (60 cases and 60 controls). Sampling using probability sampling technique by means of simple random sampling. The results showed the risk factors of type 2 Diabetes Mellitus disease i.e body mass index P-value = 0.003, OR = 3.237 (CI 95% 1,529-6,853), upper arm circumference P-value = 0.001, OR = 3.923 (CI 95% 1,806-8,524), abdominal circumference P-value = 0.000, OR = 5.675 (CI 95% 2,560-12,580), and sleep quality P-value = 0.001, OR = 5.923 (CI 95% 2,056-17,064). The conclusion is that body mass index, upper arm circumference, abdominal circumference, and sleep quality are risk factors for type 2 diabetes mellitus disease in patients visiting in Puskesmas Wawotobi Konawe district in 2020. The community is expected to play an active role in preventing the occurrence of type 2 diabetes mellitus.